Different patterns of attentional bias in antenatal and postpartum depression. Issue 11 (18th October 2017) - Edvinsson, Åsa; Skalkidou, Alkistis; Hellgren, Charlotte; Gingnell, Malin; Ekselius, Lisa; Willebrand, Mimmie; Sundström Poromaa, Inger
Abstract: Background: Biased information processing in attention, memory, and interpretation is proposed to be central cognitive alterations in patients with major depressive disorder, but studies in women with peripartum depression are scarce. Because of the many similarities with depression in nonperipartum states as regards symptom profile and risk factors, we hypothesized that women with antenatal and postpartum depression would display attentional bias to negatively and positively valenced words. Methods: One hundred and seventy‐seven pregnant and 157 postpartum women were included. Among these, 40 suffered from antenatal depressive disorder and 33 from postpartum depressive disorder. An emotional Stroop task with neutral, positive, negative, and negatively valenced obstetric words was used. Results: No significant difference in emotional interference scores was noted between women with antenatal depression and nondepressed pregnant women. In contrast, women with postpartum depression displayed shorter reaction times to both positive ( p = .028) and negative ( p = .022) stimuli, compared with neutral words. Pregnant women on antidepressant treatment displayed longer reaction times to negatively valenced obstetric words in comparison with untreated depressed women ( p = .012), and a trend toward greater interference in comparison with controls ( p = .061). Conclusions: In contrast with the hypothesis, we found no evidence of attentional bias to emotionally valenced stimuli in women with untreated peripartum depression. However, the shorter reaction times to emotional stimuli in women with postpartum depression may indicate emotional numbing, which in turn, is a functional impairment that may have repercussions for child development and well‐being. Our findings emphasize the need to identify and treat women with postpartum depression at the earliest possible time point to ensure swift recovery and support for the family. Abstract : Biased information processing in attention, memory, and interpretation is proposed to be central cognitive alterations in patients with major depressive disorder, but studies in women with peripartum depression are scarce. In this relatively large sample of pregnant and postpartum women ( n = 334), we studied attentional bias by use of the emotional Stroop task. The overall results displayed no evidence of attentional bias to emotionally valenced stimuli in women with untreated peripartum depression. However, shorter reaction times to the emotional stimuli in women with postpartum depression may indicate emotional numbing, which in turn, is a functional impairment that may have repercussions for child development and well‐being.